Favorite African folktales - Mandela, Nelson, 1918- (New York : W. W. Norton, 2004)
A collection of some of the oldest African tales, selected by Nelson Mandela, former president of South Africa, which presents such themes as cunning animals, magic spells, and people who change forms.
Originally published in South Africa in 2002 under the title: Madiba magic: Nelson Mandela's favourite stories for children.
Keywords: Mandela, Nelson -- 1918-; Nelson Mandela's favorite African Falktales; Tales -- Africa; Folklore -- Africa; Madiba magic